Respons Fisiologis Tembakau (Nicotiana tabacum L. ‘Bligon’) dengan Pemberian Pupuk Nitrogen pada Kondisi Kekeringan - Salma Nur Majidah; Siti Nurbaiti; Diah Rachmawati (Universitas Gadjah Mada, 2025)
Tobacco is an important agricultural commodity in Indonesia, but it is vulnerable to drought due to climate change. This study aimed to analyze the physiological response of tobacco plants (Nicotiana tabacum L. 'Bligon') to nitrogen fertilizer application under drought conditions. The experiment was arranged in a Randomized Complete Block Design with a combination of three urea fertilizer doses (0.6; 1.2; 1.8 g/ 5 kg of growing media) and three levels of field capacity levels (100; 75; 50%). Each treatment combines three replications. Parameters observed included plant growth and physiological traits, and the data were analyzed using analysis of variance followed by Duncan’s test at a 5% significance level. The results showed that nitrogen application significantly affected the physiological response of tobacco plant under drought conditions. The 0.6 g nitrogen dose showed a low effect on physiological and growth parameters. The 1.2 g doses moderately increased carotenoids and membrane stability index (MSI). While 1.8 g significantly improved chlorophyll, MSI, and growth parameters. These results indicate a positive correlation between physiological responses and increasing urea doses.